MANAGEMENT OF ORAL EPITHELIAL DYSPLASIA- A REVIEW - Krisna Malay, Kausalyah; S, Gheena; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Aim: To review the management strategies for the treatment of oral epithelial dysplasia.Objective: The purpose of this review is to analyse the effectiveness of success rate of the treatments given for oral epithelial dysplasia and the cure rate.Background: Oral epithelial dysplasia is a relatively common premalignantcondition;oral dysplasia can only be diagnosed histologically. It is usually seen in the form of leukoplakia due to its non-scrapable white patches characteristic. It is a lesion that can progress into malignancy (cancer).Reason: At present, the only effective treatment is surgical excision for oral epithelial dysplasia, but this method has high risk of recurrence. Surgical excision of large lesion may require extensive reconstruction technique. To avoid these disadvantages, a general dental practitioner should have more knowledge about the treatments for this lesion.